Experimental investigation of right‐left flow balance concepts for a total artificial heart. Issue 4 (18th November 2020) - Diedrich, Mario; Hildebrand, Stephan; Lommel, Moritz K.; Finocchiaro, Thomas; Cuenca, Elena; De Ben, Heiko; Schmitz‐Rode, Thomas; Steinseifer, Ulrich; Jansen, Sebastian
Abstract: A total artificial heart (TAH) must be designed to autonomously balance the flows of the systemic and pulmonary circulation to prevent potentially lethal lung damage. The flow difference between the systemic and pulmonary circulation is mainly caused by the bronchial (arteries) shunt flow and can change dynamically. The ReinHeart TAH consists of only one actuator that ejects blood alternately from the right and left pump chamber. This design entails a coupling of the right and left stroke and thus, complicates the independent adaptation of the right and left flow. In this experimental study on the ReinHeart TAH, four concepts to keep the flows well balanced were investigated using an active mock circulation loop for data acquisition. Three concepts are based on mechanical design changes (variation of pusher plate shape, flexible right pump chamber housing, and reduced right stroke volume) to achieve a static flow difference. In combination with these static concepts, a concept influencing the ratio of systole and diastole duration to respond to dynamic changes was studied. In total, four measurement series, each with 270 operating points, to investigate the influence of circulatory filling volume, heart rate, bronchial shunt flow, and lung resistance were recorded. In the course of this study, we introduce a concept deviation indicator, providing information about the efficiency of the concepts to balance the flows based on changes in lung's blood pressures. Furthermore, the distribution of the measured data was evaluated based on bubble plot visualizations. The investigated variation of the right pusher plate shape results in high lung pressures which will cause lethal lung damage. In comparison, a flexible right pump chamber housing shows lower lung pressures, but it still has the potential to damage the lungs. Reducing the stroke volume of the right pump chamber results in proper lung pressures. The flow balance can dynamically be influenced with a positive effect on the lung pressures by choosing a suitable systole‐diastole‐ratio. The results of this study suggest that an adequate right‐left flow balance can be achieved by combining the mechanical concept of a reduced right stroke volume with an active control of the systole‐diastole‐ratio. Abstract : This study investigates four concepts to reach a proper right left flow balance in a TAH with a coupled right and left stroke. The evaluation of the concepts is based on a Concept Deviation Indicator (CDI) introduced in this study, which allows an evaluation based on the lung pressures over a wide range of working points, which were recorded with a mock circulation loop.